SPE Annual Technical Conference and Exhibition 2017
DOI: 10.2118/187096-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism Study of Wettability and Interfacial Tension for EOR Using Silica Nanoparticles

Abstract: Wettability alteration and interfacial tension (IFT) reduction are two important mechanisms for enhanced oil recovery (EOR). The introduction of nanotechnology from the fields of Biology and Material Science to the application in EOR is emerging because nanoparticles have the potential to alter formation factors like wettability and fluid properties like IFT and viscosity. However, a systematic literature review shows that ambiguity exists regarding whether nanoparticles can change wettability and IFT or not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…The movement behaviour of nanoparticles in porous media has been investigated widely, focusing on the flow, rheological behaviour and adsorption of the nanoparticles on rocks. Oil displacement mechanisms by new nanoparticles are still not explained enough and need more investigation (Agi et al 2018); however, the EOR mechanisms of nanofluids are summarised as follows: disjoining pressure, pore channel plugging, increasing the viscosity of injection fluids, IFT reduction, wettability alteration, and preventing asphaltene precipitation (Jiang et al 2017;Ortega et al 2016;Tarek 2015). Figure 1 presents a schematic of the most common nanofluid EOR mechanisms.…”
Section: The Mechanisms Of Wettability Alteration By Nanofluid Floodingmentioning
confidence: 99%
See 1 more Smart Citation
“…The movement behaviour of nanoparticles in porous media has been investigated widely, focusing on the flow, rheological behaviour and adsorption of the nanoparticles on rocks. Oil displacement mechanisms by new nanoparticles are still not explained enough and need more investigation (Agi et al 2018); however, the EOR mechanisms of nanofluids are summarised as follows: disjoining pressure, pore channel plugging, increasing the viscosity of injection fluids, IFT reduction, wettability alteration, and preventing asphaltene precipitation (Jiang et al 2017;Ortega et al 2016;Tarek 2015). Figure 1 presents a schematic of the most common nanofluid EOR mechanisms.…”
Section: The Mechanisms Of Wettability Alteration By Nanofluid Floodingmentioning
confidence: 99%
“…Disjoining pressure is defined as the pressure required for removing fluids which are in contact with the reservoir rocks due to the adhesion force of fluids/solid surface (Jiang et al 2017). Theoretical and experimental investigations show that the nanofluids reduce oil adsorption on a rock surface by entering a structural disjoining force (film) between the oil and the rock surface and then creating a wedge film structure on the rock surface.…”
Section: Disjoining Pressurementioning
confidence: 99%
“…The ability of nanoparticles to alter the wettability has been extensively studied. Contact angle measurements show that different types of nanoparticle (silicon dioxide, iron oxide, aluminum oxide and titanium dioxide) can reduce contact angle between oil and water, making surface more water wet regardless of initial surface wettability [13][14][15][16]. Microfluidic flooding experiments show that nanofluid flooding can alter wettability of glass grains.…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid the above problems caused by the addition of surfactants into nanofluids, Jiang et al (2017) investigated the effect of nanoparticles addition on the wettability and oil recovery without adding any other chemicals other than silica nanoparticles into the nanofluid. They found that bare silica nanoparticles had an impact on wettability.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in nanofluid concentration and a decrease in nanoparticle size both result in a decrease in contact angle (makes the substrate more water-wet), which increase the oil recovery by about 8.7%. Jiang et al (2017) reported that bare silica nanoparticles had no influence on IFT between n-decane and nanofluid.…”
Section: Introductionmentioning
confidence: 99%